Body image and food disorders: evidence from a sample of European women - Joan Costa-Font; Mireia Jofre-Bonet (Center for Economic Studies and ifo Institute (CESifo), 2008)
Excessive preoccupation for self-image has been pointed out as an essential factor explaining food disorders. This paper draws upon Akerlof and Kranton (2000) to model how self-image and others' appearances influence health related behaviours. We estimate the influence of peers' image on the likelihood of anorexia and self-image using data from a cross sectional European representative survey for 2004. We follow a two-step empirical strategy. First, we estimate the probability that a woman is extremely thin and, at the same time, she sees herself as too fat. Our findings reveal that peers' average Body Mass Index decreases the likelihood of being anorexic. Second, we take apart the two processes and estimate a recursive probit model of being very thin and perceiving one self as being too fat. Although peers' Body Mass Index decreases the likelihood of being very thin but increases that of seeing one self as too fat, the unobservables explaining both processes are significantly correlated.
Keywords: I12; Q18; 330; Self-image; identity; body image; eating disorders; anorexia; Ernährungsgewohnheit; Frauen; Persönlichkeitspsychologie; Konsuminterdependenz; Europa